2023
DOI: 10.1021/acs.bioconjchem.3c00200
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan-PNA gc Conjugates Self-Assemble to Form Fibers

Abstract: Peptide nucleic acids and their conjugates to peptides can selfassemble and generate complex architectures. In this work, we explored the selfassembly of PNA dimers conjugated to the dipeptide WW. Our studies suggest that the indole ring of tryptophan promotes aggregation of the conjugates. The onset of fluorescence is observed upon self-assembly. The structure of selfassembled WWgc is concentration-dependent, being spherical at low concentrations and fibrous at high concentrations. As suggested by molecular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…This structure represented the dimeric arrangement of the WW dipeptide units. The selected dimeric structure was then utilized to develop WWgc conjugates (g and c stand for guanine and cytosine PNA monomeric units), which are essential for the formation of WWgc fibers [45]. Overall, the study demonstrated how molecular docking techniques could be employed to investigate the self-aggregation of amino acid units and to model the formation of higher-order structures such as WWgc fibers.…”
Section: Self-assembly and Biological Properties Of The Non-natural A...mentioning
confidence: 99%
See 1 more Smart Citation
“…This structure represented the dimeric arrangement of the WW dipeptide units. The selected dimeric structure was then utilized to develop WWgc conjugates (g and c stand for guanine and cytosine PNA monomeric units), which are essential for the formation of WWgc fibers [45]. Overall, the study demonstrated how molecular docking techniques could be employed to investigate the self-aggregation of amino acid units and to model the formation of higher-order structures such as WWgc fibers.…”
Section: Self-assembly and Biological Properties Of The Non-natural A...mentioning
confidence: 99%
“…This study demonstrates the utility of molecular docking simulations in elucidating the self-assembly mechanism of peptide-based materials, providing valuable insights into their structural organization and potential applications in supramolecular gelation. In the paper by Mosseri et al, molecular docking was utilized to construct a model of a WWgc fiber starting from a WW dipeptide unit [45]. The dipeptide unit was used as both a receptor and a ligand in the Haddock software [46][47][48][49][50] to predict its dimeric form through molecular docking techniques.…”
Section: Self-assembly and Biological Properties Of The Non-natural A...mentioning
confidence: 99%